MODERN APPROACHES AND OPPORTUNITIES OF DEVELOPING INCLUSIVE TOURISM ON THE EXAMPLE OF UZBEKISTAN (Universal International Scientific Journal, 2026)
This study is devoted to the study of modern directions and practical mechanisms for the development of inclusive tourism. The work analyzed the issues of creating a comfortable tourist environment for people with disabilities through the introduction of digital technologies, mobile applications, interactive maps and universal design principles. The results of the study showed that inclusive tourism can improve the quality of service provision, form a new market segment and strengthen the competitiveness of the tourism industry. It was also substantiated that this direction serves to ensure economic efficiency and improve state policy.
Keywords: inclusive tourism; tourism services market; digital technologies